Use of stable nitrogen isotopes to track plant uptake of nitrogen in a nature-based treatment system - Cecchetti, A.R. (2021)
We applied this new method to a pilot-scale horizontal levee system (i.e., a subsurface constructed wetland) over a two-year monitoring period, during which 14% of nitrogen in plants was wastewater-derived on average and the remaining plant nitrogen was obtained from the soil. Analysis of nitrogen isotopes indicated substantial spatial variability in the wetland: 82% of nitrogen in plants within the first 2 m of the slope came from wastewater while less than 12% of plant nitrogen in the remainder of the wetland originated from wastewater. By combining these source contributions with remote-sensing derived total biomass measurements, we calculated that 150 kg N (95% CI = 50 kg N, 330 kg N) was taken up and retained by plants during the two-year monitoring period, which corresponded to approximately 8% of nitrogen removed in the wetland. Nitrogen uptake followed seasonal trends, increased as plants matured, and varied based on design parameters (e.g., plant types), suggesting that design decisions can impact this removal pathway. This new method can help inform efforts to understand nitrogen cycling and optimize the design of nature-based nutrient control systems.